Formulating a Comprehensive System of Contractual Excuses in the Iranian Legal Order - Seyyed Mohammad Hasan Momeni; Amir Mahdi Ghorban Poor (پژوهش‌نامه حقوق اسلامی)
‌ ∴ Introduction ∴ ‌The enforceability of contractual obligations is foundational to legal and economic systems. However, certain circumstances may obstruct an obligor’s ability to fulfill these obligations, necessitating what is termed "Contractual Excuses"—doctrines and provisions that relieve the obligor, fully or partially, from liability under specific conditions. In Common Law, these doctrines are well-established, permitting partial or full exoneration based on predefined criteria. However, Iranian law, deeply rooted in Shi’a jurisprudence, approaches contractual excuses uniquely, emphasizing fairness, justice, and religious principles. Shi’a jurisprudence, as a primary influence on Iranian legal principles, mandates that the conceptualization of contractual excuses aligns with religious doctrines, which introduces distinct interpretative challenges and classifications that differ from Western legal frameworks. This article addresses the need for a structured, criteria-based categorization of contractual excuses, aiming to clarify their roles within the Iranian legal system, thereby facilitating more consistent legal outcomes and reinforcing justice in contractual relationships.‌ ∴ Research Question ∴ ‌This study primarily seeks to answer the question: What are the types and criteria for classifying contractual excuses within the context of Shi’a jurisprudence and Iranian law? In addressing this question, the research aims to identify and delineate the scope and boundaries of contractual excuses within Iranian law, distinguishing them from comparable doctrines in other legal systems. The goal is to clarify how these excuses operate, their limitations, and their significance in preserving the balance between contractual obligations and fairness, especially when circumstances obstruct full compliance.‌ ∴ Research Hypothesis ∴ ‌This article provides an overview of the comprehensive system of contractual excuses in Islamic jurisprudence and Iranian law, aiming to categorize them systematically and does not present a specific hypothesis.‌ ∴ Methodology & Framework, if Applicable ∴ ‌The research adopts a doctrinal methodology, focusing on a detailed examination of Islamic jurisprudence, statutory laws, and legal doctrines relevant to the classification of contractual excuses in Iran. By analyzing primary legal texts, religious doctrines, and scholarly interpretations from prominent Shi’a jurists, the study synthesizes a comprehensive framework for understanding contractual excuses within the Iranian context. The research structure is divided into three progressive stages: (1) a conceptual analysis of contractual excuses, emphasizing Shi’a jurisprudential principles; (2) the establishment of classification criteria for different types of excuses, tailored to Iranian law; and (3) an explication of these excuses based on practical and doctrinal applications. The framework underscores a comparative approach, drawing distinctions between Iranian and Common Law doctrines to highlight the unique aspects of the Iranian legal approach to contractual excuses.‌ ∴ Results & Discussion ∴ ‌The research findings highlight a structured and detailed classification of contractual excuses within Iranian law, with a foundation rooted in Shi’a jurisprudence. This framework delineates two primary categories of excuses: Ta’azzor (impossibility of performance) and Ta’assor (severe hardship in performance). Each category reflects different levels of difficulty that might prevent an obligor from fulfilling contractual obligations, and both are distinguished by the nature and extent of the impediment. Through a doctrinal analysis, the study identifies and classifies fourteen specific types of excuses under each category, resulting in a total of twenty-eight distinct conditions that legally justify contract modification, annulment, rescission, or other adjustments.     The discussion reveals that Iranian law’s approach to contractual excuses is more nuanced than many other legal frameworks, such as Common Law, where excuses are often addressed as exceptions. By contrast, the Iranian system evaluates each instance of impossibility and hardship in performance based on criteria such as timing, personal versus general nature of the excuse, severity, and the influence of the excuse on contractual performance.‌ ∴ Conclusion ∴ ‌The study concludes that Iranian law, informed by Islamic jurisprudence, offers a systematic approach to contractual excuses, accommodating both impossibility and hardship scenarios. The distinct classification of impossibility and hardship in performance provides a robust framework that respects the intent and obligations within contracts while acknowledging legitimate barriers. With fourteen identified types of excuses under each category, resulting in twenty-eight possible scenarios, Iranian law enables precise application of legal remedies suited to the excuse type. This approach ensures that contractual obligations are balanced with fairness, where mere obstacles do not automatically trigger generic legal principles but instead prompt a specific response based on the unique nature and characteristics of the excuse encountered.